Assessment in English First Additional Language (EFAL) following the principles of outcomes-based education - Letsoalo, Kgwahle Bernard (My University, 2009)
The assessment of the current school reform effort emphasizes the neeed to improve the education of all learners. Assessing the academic achievement of every learner is an essential part of this reform, but one that presents a challenge for most schools, school districts and provinces. Traditional assessment practices have tended to exclude learners who are denied access to important educational opportunities that are based on assessment results. This problem is often more pronounced among learners who have to do Grade 9. This study focuses on assessment and discusses the advantages and challenges experienced by learners and educators. The aim of this study, therefore, is to assess educators’ success in the implementation of OBE assessment principles of English First Additional Language (EFAL) in Grade 9. This study was prompted by educator assessments, which have kept interesting the researcher because of traditional assessments which are at odds with OBE. Most importantly, assessment is no longer practised and determined in traditional ways. The educator must assess, in detail, the knowledge, skills and dispositions that learners must develop in order to achieve learning outcomes. The researcher recommends assessment to include English langauge learners, increase school accountability for all learners, have a shared vision of learner goals and standards, have an authentic picture of learning, and reflect assessment.
Thesis (M.A.(Language Education)) -- University of Limpopo, 2009
Keywords: Outcomes-based education; Language assessment; Academic achievement assessment; English teaching -- Study and teaching; Competency-based education - South Africa